Marrow Hematopoietic Stem Cells Revisited: They Exist in a Continuum and are Not Defined by Standard Purification Approaches; Then There are the Microvesicles - Quesenberry, Peter J.; Goldberg, Laura; Aliotta, Jason; Dooner, Mark (Frontiers in Oncology, 2014)
Current concepts of hematopoiesis are encompassed in a hierarchical stem cell model. This developed initially from studies of colony-forming unit spleen (CFU-S) and in-vitro progenitors for different cell lineages, but then evolved into a comprehensive model of cells with different in vivo differentiative and proliferative potential. These cells were characterized and purified based largely on expression of a variety of lineage specific and stem cell specific surface epitopes. Monoclonal antibodies bound to these epitopes and were then used to physically and fluorescently separate different classes of these cells. The gold standard for the most primitive marrow stem cells was long-term multilineage repopulation and renewal in lethally irradiated mice. Progressive work seemed to have clonally defined a lineage negative Sca-1+, c-kit+ CD150+ stem cell with great proliferative, differentiative and renewal potential. This cell was stable and in the G0 phase of cell cycle. However, continued work in our laboratory indicated that the engraftment, differentiation, homing, and gene expression phenotype of the murine marrow stem cells continuously and reversibly changes with passage through cell cycle. Most recently, using cycle defining supravital dyes and fluorescent activated cell sorting and S-phase specific tritiated thymidine suicide, we have established that the long-term repopulating hematopoietic stem cell is a rapidly proliferating, and thus a continually changing cell; as a corollary it cannot be purified or defined on a clonal single cell basis. Further in vivo studies employing injected and ingested BrdU, showed that the G0 lin-Sca-1, c-kit + Flt3- cell was rapidly passing through cell cycle. These data are explained by considering the separative process: the proliferating stem cells are eliminated through the selective separations leaving non-representative dormant G0 stem cells. In other words they throw out the real stem cells with the purification. This sys